2019
DOI: 10.1017/s0031182018002172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data show Clinostomoides Dollfus, 1950 is a junior synonym of Clinostomum Leidy, 1856, with redescription of metacercariae of Clinostomum brieni n. comb.

Abstract: The genus Clinostomoides Dollfus, 1950 was erected to accommodate a single worm from Ardea goliath sampled in the Belgian Congo. The specimen was distinguished from other clinostomids by its large size and posterior genitalia. In the following years, metacercariae of Clinostomoides brieni, have been described in Clarias spp. in southern and western Africa. A few authors have referred to Clinostomum brieni, but all such usages appear to be lapsus calami, and the validity of Clinostomoides remains widely accepte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 26 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Data presented in this study reflects the complexity and problematic nature of the morphologically based classification involving clinostomids, complementing the recent study of Caffara et al (2019) that molecularly confirmed the placement of the large-sized Clinostomoides brieni Dollfus, 1950 within Clinostomum ; besides the large size, C . brieni further differs from the 'typical' Clinostomum species by having the genital pore post-testicular and the whole genital complex extremely close to the posterior end.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Data presented in this study reflects the complexity and problematic nature of the morphologically based classification involving clinostomids, complementing the recent study of Caffara et al (2019) that molecularly confirmed the placement of the large-sized Clinostomoides brieni Dollfus, 1950 within Clinostomum ; besides the large size, C . brieni further differs from the 'typical' Clinostomum species by having the genital pore post-testicular and the whole genital complex extremely close to the posterior end.…”
Section: Resultssupporting
confidence: 72%
“…Diagnosis: As in Kanev et al (2002) , updated (broader concept) by Caffara et al (2019) , but with the following change: Body middle-sized to very large (5–100 mm long), slender to stout, may be attenuated anteriorly. Space between ventral sucker and anteriormost vitelline follicles may be void of organs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Clinostomum currently contains 22 putative species (Supplementary Table S1). These species were validated either morphologically, molecularly, or using both sources of information through an integrative taxonomy approach (e.g., Sereno-Uribe et al 2013Pérez-Ponce de León et al 2016;Locke et al 2019;Caffara et al 2017Caffara et al , 2019Caffara et al , 2020. Still, nine molecularly recognized species based on metacercarial stages need to be described and named (Locke et al 2015; Pérez-Ponce de León et al 2016;Montes et al 2020).…”
Section: Introductionmentioning
confidence: 99%